The role of TRECs/KRECs as immune indicators that reflect immunophenotypes and predict the risk of infection in systemic autoimmune diseases - Takuji Itakura; Hirokazu Sasaki; Tadashi Hosoya; Natsuka Umezawa; Tetsuya Saito; Hideyuki Iwai; Hisanori Hasegawa; Hiroyuki Sato; Akihiro Hirakawa; Kohsuke Imai; Tomohiro Morio; Naoki Kimura; et al. (Immunological Medicine)
T cell receptor rearrangement excision circles (TRECs) and immunoglobulin κ-deleting recombination excision circles (KRECs) represent the lymphopoiesis capacity, widely used for newborn screening of inborn errors of immunity. To clarify the significance of TRECs and KRECs as immune indicators in patients with systemic autoimmune diseases, we prospectively evaluated TREC and KREC levels with qPCR, lymphocyte phenotypes with flow cytometry, along with lymphocyte counts and serum immunoglobulin levels in peripheral blood samples from newly diagnosed patients. Each variable was assessed before immunosuppressive treatments (baseline), 3-, 6-, and 12-months after the treatment. Severe infections were recorded until 6 months after treatment. Among 35 patients, TREC and KREC levels were associated positively with the proportion of recent thymic emigrants, naïve T and B cells at all the timepoints. TREC and KREC levels decreased after treatment. The ratios of TREC and KREC levels under treatment to baseline were significantly lower in patients with severe infection than those without. In conclusion, TREC and KREC levels reflect peripheral blood immunophenotypes, specifically recent-emigrated T and B cells, in patients under treatment-naïve and immunosuppressive conditions. The longitudinal changes in TREC and KREC levels were beneficial markers for predicting the risk of severe infection during immunosuppressive treatments.